What Is New in Pediatric Bone Health. Issue 8 (7th September 2021) - Beck, Jennifer J.; Mahan, Susan T.; Nowicki, Philip; Schreiber, Verena M.; Minkowitz, Barbara
Abstract : Background: This review paper aims to report on the last 5 years of relevant research on pediatric bone health in regard to nutrition and obesity, ethnic disparities, common orthopaedic conditions, trauma, spine, and sports medicine. Methods: A search of the PubMed database was completed using the following terms: bone health, Vitamin D, pediatric, adolescent, sports medicine, fractures, spine, scoliosis, race, ethnicity, obesity, Slipped Capital Femoral Epiphysis, Osteogenesis Imperfecta, Duchenne's Muscular Dystrophy, neuromuscular, and cancer. Resultant papers were reviewed by study authors and determined to be of quality and relevance for description in this review. Papers from January 1, 2015 to August 31, 2020 were included. Results: A total of 85 papers were selected for review. General results include 7 key findings. (1) Obesity inhibits pediatric bone health with leptin playing a major role in the process. (2) Socioeconomic and demographic disparities have shown to have a direct influence on bone health. (3) Vitamin D deficiency has been linked to an increased fracture risk and severity in children. (4) Formal vitamin D monitoring can aid with patient compliance with treatment. (5) Patients with chronic medical conditions are impacted by low vitamin D and need ongoing monitoring of their bone health to decrease their fracture risk. (6) Vitamin D deficiency in pediatrics has been correlated to low back pain, spondylolysis, and adolescent idiopathic scoliosis. Osteopenic patients with AIS have an increased risk of curve progression requiring surgery. Before spine fusion, preoperative screening for vitamin D deficiency may reduce complications of fractures, insufficient tissue repair, loosening hardware, and postoperative back pain. (7) Increasing youth sports participation has resulted in increased bone health related injuries. However, improved understanding of Relative Energy Deficiency in Sport effects on bone health has recently occurred. Conclusions: Increasing awareness of bone health issues in children will improve their recognition and treatment. Further research is needed on diagnosis, treatment, outcomes, and most importantly prevention of pediatric bone health diseases.